2022
DOI: 10.3389/fnhum.2022.1021375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation on motor skills learning in healthy adults through the activation of different brain regions: A systematic review

Abstract: ObjectiveThis systematic review aims to analyze existing literature of the effects of transcranial direct current stimulation (tDCS) on motor skills learning of healthy adults and discuss the underlying neurophysiological mechanism that influences motor skills learning.MethodsThis systematic review has followed the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses. The PubMed, EBSCO, and Web of Science databases were systematically searched for relevant studies that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Polarization direction depends on axonal orientations within the electric field ( 18 ). Effects are concentrated under the electrodes; though polarity, electrode size and placement precision, including the duration of stimulation are variables that can potentially influence distant neural networks ( 19 ). tDCS studies exploring chronic pain conditions during the last 30 years have mainly targeted the motor cortex [M1] ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polarization direction depends on axonal orientations within the electric field ( 18 ). Effects are concentrated under the electrodes; though polarity, electrode size and placement precision, including the duration of stimulation are variables that can potentially influence distant neural networks ( 19 ). tDCS studies exploring chronic pain conditions during the last 30 years have mainly targeted the motor cortex [M1] ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) applied to the primary motor cortex (M1) has been shown in numerous studies to increase primary motor cortex excitability and improve motor skill learning in tasks performed with the hand and arm [1][2][3][4][5]. Most M1-tDCS studies have shown skill improvements of approximately 10-15% during or immediately after a single tDCS application when compared to the practice of a motor task alone in the same conditions [1].…”
Section: Introductionmentioning
confidence: 99%